Spread and control of pistachio dieback in Australia - Taylor C.; Emmett R.W.; Facelli E.; Scott E.S.; Sedgley M. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The probable causal pathogen of bacterial dieback of pistachios in Australia has been tentatively identified as Xanthomonas translucens. Bacterial dieback of pistachio affects orchards across the growing region of south-eastern Australia. Symptoms include decline, dieback, internal staining, trunk and limb lesions and can lead to tree death. Xanthomonas has been recovered from pruning tools after pruning infected orchard trees. Experiments were conducted to determine possible pathogen entry points, mechanisms of spread and to assess control strategies. Xanthomonas was recovered from the leaves, shoots and trunk of trees inoculated by placing drops of bacterial suspension on pruning wounds on one year-old shoots of potted trees. Copper sprays did not prevent infection when applied immediately after inoculation of pruning wounds in the glasshouse.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)